Changing aspects of bonded labour in India - Hamilpurker, J. L. (Delhi, 1989)
Of several problems in India, the problem of bonded labour has recently been the focal point of all politicians, social reformers and sociologists. The system of bonded labour is imcompatible with the current political and social ideologies and is dangerous and detrimental to the well being of society. It has encouraged social injustice and economic imbalance. It has come down as a legacy of the old feudal system and therefore calls for immediate and effective measures for the eradication of the system. The system of bonded labour is known differently in different parts of the country. The identification of bonded labour in modernizing India is a very crucial issue and needs a more scientific effort. This issue has been taken more seriously by making it evident as a debt based one. The plight of the bonded labourer is understood in terms of studying the indepth master-servant relations, causes of bondage and the rehabilitative inadequate measures initiated by government. This study stresses more determined and vigorous thinking, proper identification and more permanent rehabilitative measures to check the re-entry of an individual as bonded labourer after his rehabilitation. The entire issue would becorde more meaningful if the agrarian context is taken into account while attending the rehabilitation task of bonded labourers. It has highlighted the need for a dynamic appraisal of plans and policies for eradicating the bondage.
Keywords: Bonded labour India